1974
DOI: 10.1037/h0036904
|View full text |Cite
|
Sign up to set email alerts
|

Membership characteristics of the Division of School Psychology of the American Psychological Association.

Abstract: of the specialties within psychology that has been receiving increasing attention is school psychology. Within the American Psychological Association, the Division of School Psychology (Division 16) has steadily gained in membership, activity, and influence. At the time this article was written (summer 1973), Division 16 was fifth in total membership among the divisions and second only to Division 12 (Clinical) in number of representatives in Council.Despite its size and visibility, there seems to be relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1976
1976
1977
1977

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Closer to home, Kimmel et al, (1974) stated that only one of 20 presidents of SEPA was female and no women participated on the 1973 executive. Contrary to the situation in the SEPA, Cardon (1974) commented that although women represented less than 40 percent of the membership of the APA Division of School Psychology they held more than half of the seats on the Executive Committee. Myers (Note 2) noted that of 80 APA presidents only five percent were women.…”
Section: Professional Commitments and Contributionsmentioning
confidence: 82%
See 2 more Smart Citations
“…Closer to home, Kimmel et al, (1974) stated that only one of 20 presidents of SEPA was female and no women participated on the 1973 executive. Contrary to the situation in the SEPA, Cardon (1974) commented that although women represented less than 40 percent of the membership of the APA Division of School Psychology they held more than half of the seats on the Executive Committee. Myers (Note 2) noted that of 80 APA presidents only five percent were women.…”
Section: Professional Commitments and Contributionsmentioning
confidence: 82%
“…With respect to all recipients of doctorates in psychology in 1970, men gravitated toward academic settings while women were more likely to find employment in industry, business or government (Astin, 1972). Cardon (1974) noted that within the American Psychological Association (APA) Division of School Psychology, 85 percent of the female members were employed in nonuniversity settings as compared with 68 percent of the male members. Astin et al (1973) reported that only 10 percent of psychology faculty were women although 25 percent of the APA membership is female.…”
Section: Census and Locationmentioning
confidence: 99%
See 1 more Smart Citation